ANALYSIS OF WEB-BASED COLLEGE ENGLISH TEACHING FROM 2000 TO 2017 IN CHINA - Zhang, Baohuan (Universitas Nusantara PGRI Kediri, 2020)
Based on 812 papers on web-based college English teaching published in Chinese journals from 2000 to 2017, this study adopted modern statistical methods to explore the spatio-temporal development of the research. The results revealed the research on web-based college English teaching started in 2000 and had been increasing from 2006 to 2011; however, scholars’ attention to it was on the decline after 2012. During the period of 2000 -2017, the average annual number of papers published in Chinese journals was up to 45 while that in core journal was only 4. Meanwhile, there were significantly spatial differences. The research on web-based college English teaching in China has mainly focused on eastern region, particularly, Beijing and Guangdong as two main research regions, its average annual number of papers issued in core journals accounted for 9.5% of the total amount of the country respectively. We can see many well-known experts in